Social perceptions of schooled violence among educated adolescents: Field study in intermediate education institutions - Hadj khelouf, Fatima Zohra; Hamani, Hazem (Journal of Human Sciences, 2022)
The aim of this study was to learn about the social perception of school violence among middle schoolchildren. In this study, we relied on the descriptive curriculum and used the Abric hierarchical deterioration method on a sample estimated at 30 adolescents in middle education to learn the structure and content of social perceptions. The study took place at averages in the municipality of Tadjenanet, Mila State. The results of our study concluded :                           -Pupils had no clear perception of school violence, but she explained that the nature of pupils' perceptions was predominantly about violence in general.                -The stability index of perceptions was not stable, and the components of the central nucleus were about "multiplication" elements.                -With the beginning of forming a new nucleus.